Influence of boron and organic matter on the changes in soil biological properties and yield of rape (Brassica campestris) in an aeric endoaquept - MANDAL, MITALI; DAS, DILIP KUMAR (The Indian Journal of Agricultural Sciences, 2014)
Field experiments were conducted during winter seasons of 2006 -07 and 2007-08 to study the influence of boron and organic matter application on the changes in soil biological properties in an aeric endoaquept (pH,7.5;organic carbon content, 0.61%; CaCl2–extractable boron 0.32 mg/kg) growing rape (Brassica campestris L.) as a test crop. The results reveal that non-symbiotic nitrogen fixing bacteria (NFB), non symbiotic nitrogen fixing capacity, phosphate solubilising micro-organisms (PSM), phosphate solubilising capacity (PSC) and microbial biomass carbon (MBC) have been found to be influenced with different treatments, being recorded highest (90.45, 69.29 × 105/g soil; 11.73, 9.63; 80.29, 63.28 mg of N2 fixed/g of soil/g of sucrose; 0.038, 0.032 mg/g dry soil and 159.48, 149.58 µg/g dry soil respectively) in the treatment T4 where lower level (0.5 kg/ha) of boron as calbor and organic matter at 5 tonnes/ha was applied along with recommended levels of N, P2O5 and K2O (80:40:40) in both rhizosphere (R) and non- rhizosphere (NR) soils. The yield of rape was also recorded highest (8.95 q/ha) in the treatment T4 ( lower level (0.5 kg/ha) of boron as calbor,organic matter at 5 tonnes/ha and recommended levels of N, P2O5 and K2O ( 80:40:40 ). From the stepwise technique of multiple regression it was revealed that the NFB at R and NR, PSC at R and NR, PSM at R and NR and MBC at NR are only important predictors which can explain 99 % of total variance.